Cleaning device for egg product processing - ZHA ANCHUN; LIANG YONG; ZHU WANJING; YIN HENGBING; ZHANG WANLIN; CHEN JING (2024)
The utility model discloses a cleaning device for egg product processing, which relates to the technical field of egg processing and comprises a cleaning box. The top end of the outer wall of the cleaning box is open; a motor is fixedly connected to one side of the outer wall of the cleaning box through a fixing block. A rotating shaft is arranged at the output end of the motor, and one end of the outer wall of the rotating shaft penetrates through one side of the outer wall of the cleaning box; a placement fixing piece is arranged at one end of the outer wall of the rotating shaft in the cleaning box; the placement fixing piece comprises a placement plate; according to the egg cleaning device, eggs are fixed through the placement fixing piece, the motor drives the rotating shaft to rotate, the placement fixing piece drives the eggs to rotate, meanwhile, the first gear on the rotating shaft drives the second gear to rotate, and the pair of rotating rollers drives the set of cleaning brushes and the set of cle